Pollen Preservation in Alluvial Soils: Implications for Paleoecology and Land Use Studies. Issue 5 (1st September 2019) - Ricker, Matthew C.; Stolt, Mark H.; Zavada, Michael S.
Abstract : Core Ideas: Floodplain soils preserve pollen that can reconstruct past climate and land uses. Pre‐evaluation of soil properties will save future researchers time and money. Alluvial pollen preservation data expand where paleoecology studies can be done. Floodplain landscapes with fluctuating water tables are nontraditional sites for palynology studies, and therefore intrinsic alluvial soil properties and their relationship to pollen preservation are poorly understood. The primary objective of this study was to identify soil properties that are most related to pollen preservation in floodplains to aid in predicting soil pollen presence and abundance. Our results indicate that all organic soil horizons had preserved pollen, whereas mineral horizons had variable pollen concentrations (range, 0–59, 000 grains g −1 soil). Mineral samples with preserved pollen (>0 grains g −1 soil) had significantly greater ( p < 0.001) soil organic matter (SOM) and silt + clay, and were located closer to the modern soil surface. Regression analyses indicated that only SOM and C/N ratios were significant predictors of pollen abundance. The guidelines developed in this study can be used to identify samples that likely contain enough pollen for palynological analysis and save future researchers considerable laboratory time, effort, and cost.